PEMIKIRAN FILOSOFIS MUHAMMAD IQBAL TENTANG PENDIDIKAN - ., Nuryamin (Jurnal Pendidikan Kreatif, 2020)
The world does not know the word stop, he continues to move in the process of becoming. Nature with everything in it is constantly changing with a series of events continuously in the form of directed and integrated changes. The whole physical, psychic, and imaginary world always moves horizontally until the archetypes are motionless and radiant, always in motion and becoming. In educational thought, the consequence of the law of becoming is the birth of a variety of philosophical thoughts in education as a development of dialectical-dialogical thinking in answering various problems in the educational area which is recognized as very broad and complex. The name Muhammad Iqbal, a thinker in the Islamic world who is concerned with the development of education who has a dynamic view by assuming that the world he lives in never stops with advancing towards its perfection. A creative and dynamic world view that refers to metaphysical, ethical and epistemological reflections can be realized through education. By referring to metaphysical reflection, the philosophical thought of education reaches the peak of its goal, namely to make students become human beings with a pattern of piety, namely the unity of the body and spirit, or the term Iqbal is a true believer. True believers are hope, work, improvement and formation, peace and harmony, not weak because of obstacles and not shunning difficulties. True believers make the attributes of God inherently in themselves. With that he was able to become a representative of God (caliph on earth).